How Do Students’ Cognitive Style Influence Their Mathematical Problem-Solving Thinking Procesess: A systematic Literature Review - Eko Yandi Raharjo; Prismadian Amalia Putri; Sudarwan Danim; Eko Risdianto (Universitas PGRI Silampari, 2025)
This study aims to explore the influence of students' cognitive styles on the thought process in solving mathematical problems through a Systematic Literature Review (SLR) approach with PRISMA guidelines. Cognitive styles such as field-dependent vs. field-independent and reflective vs. impulsive are proven to influence the way students process information, represent mathematical concepts, and apply problem-solving strategies. A review of 10 selected articles showed that active learning models such as Project-Based Learning (PjBL) and Problem-Based Learning (PBL) are more effective when adapted to students' cognitive characteristics. Field-independent and reflective students tend to excel in analytical and logical thinking, while field-dependent and impulsive students perform better in collaboration when given appropriate scaffolding. The findings also suggest a link between cognitive styles and the development of 21st century skills, particularly critical thinking, creativity, communication and collaboration. This study recommends the importance of learning design that is responsive to individual differences to support the achievement of optimal learning outcomes.